GeoGebra in Discovery Learning: Alternative Solutions for Understanding Mathematical Concepts - Putri Wardani; Machrani Adi Putri Siregar (MASI Mandiri Edukasi, 2025)
In learning, students are required to understand the concepts of problems and visualize the objects of mathematical learning discussions. However, in reality, students face difficulties in understanding and visualizing the objects discussed; learning media can help solve the problems faced by students so that the learning process is no longer conventional, which causes students to be passive. This research aims to determine whether there is an effect of GeoGebra learning media on the Discovery Learning model on students' understanding of mathematical concepts. This research uses a quasi-experimental quantitative method that tests the cause and effect between variables. The study was conducted in class XI MIA MAL UINSU as the population, with sampling carried out by randomizing classes. The sample for this study consisted of students from class XI MIA 1 as the control class and XI MIA 2 as the experimental class. Each class consists of 39 students. The instrument used is a mathematical concept understanding ability test in the form of an essay, consisting of a pretest and a posttest. The data collected were then tested using a t-test. Based on the t-test calculations with α= 0.05, the significance value obtained is 0.000, thus 0.000 < 0.05. It can be concluded that GeoGebra learning media has an effect on the Discovery Learning model on students' concept understanding. The research results regarding the impact of learning media on students' concept understanding indicate that teachers can implement this learning media in their teaching.